2002
DOI: 10.1109/jsen.2002.1000248
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen catalytic oxidation reaction on Pd-doped porous silicon

Abstract: The efficiency of Pd-doped porous silicon (PS) as a catalytic material for hydrogen sensing is studied. Pd is deposited by an electroless process on the internal surface of porous silicon. The catalytic behavior of Pd-doped PS samples is estimated and the parameters that influence the kinetics of the chemical reaction are evaluated. The catalytic activity is examined through the kinetics of the chemical reaction, which occurs in low hydrogen content mixtures with air (up to 1% v/v in air), far below the mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
2
19
0
4
Order By: Relevance
“…Improved gas response behaviour of a palladium doped porous silicon based hydrogen sensor was reported by Polishchuk et al (Polishchuk et al 1998). C. Tsamis and co workers (Tsamis et al, 2002) reported on the catalytic oxidation of hydrogen to water on Pd doped porous silicon. K. Luongo and coworkers.…”
Section: Effect Of Noble Metal Dispersion On the Surface Of Porous Simentioning
confidence: 99%
See 1 more Smart Citation
“…Improved gas response behaviour of a palladium doped porous silicon based hydrogen sensor was reported by Polishchuk et al (Polishchuk et al 1998). C. Tsamis and co workers (Tsamis et al, 2002) reported on the catalytic oxidation of hydrogen to water on Pd doped porous silicon. K. Luongo and coworkers.…”
Section: Effect Of Noble Metal Dispersion On the Surface Of Porous Simentioning
confidence: 99%
“…The nano sized voids in the bulk silicon result in a sponge-like structure of pores and channels surrounded by a skeleton of crystalline Si nano wires. Porous silicon (PS) is gaining scientific and technological attention as a potential platform mainly for its multifarious applications in sensing and photonic devices (Canham, 1997a;Pavesi & Dubos;Dimitrov,1995;Tsamis et al, 2002;Archer & Fauchet, 2003;Barillaro et al,2003). The extremely large surface to volume ratio (500m 2 /cm 3 ) of PS, the ease of its formation, control of the surface morphology through variation of the formation parameters and its compatibility to silicon IC technology leading to an amenability to the development of smart systems-on-chip sensors have made it a very attractive material.…”
Section: Introductionmentioning
confidence: 99%
“…Эти материалы обладают уникальными химическими и физическими свойствами из-за их чрезвычайно малого размера и большого отношения поверхности к объему, поэтому они открывают аль-тернативные возможности для их различных потен-циальных применений в оптоэлектронике, химиче-ском и биохимическом зондировании. Среди порис-тых полупроводников пористый GaAs получил ог-ромное внимание и наиболее интенсивно исследует-ся; однако неустойчивость физических свойств пре-пятствует его применению в серийном производстве [8][9][10]. Исследование пористого GaAs также обу-словлено его физическими свойствами, такими как термическая, механическая и химическая стабиль-ность.…”
unclassified
“…Анодное травление является наиболее подхо-дящей методикой для получения пористых слоев благодаря своей простоте и низкой стоимости изго-товления. Кроме того, применение GaAs обусловле-но его оптоэлектронными и высокоскоростными электронными свойствами из-за прямой оптической запрещенной зоны и высокой подвижности электро-нов [9,10]. Диоды Шоттки являются наиболее ши-роко используемыми выпрямляющими устройства-ми в электронной промышленности [10, 11], а также в последние десятилетия было установлено, что пористость непосредственно влияет на адсорбцион-ные характеристики материала и поэтому такие диоды все чаще применяют как датчики газов [11, 12].…”
unclassified
See 1 more Smart Citation